Influence of macro-synthetic fiber on the mechanical properties of iron ore tailing concrete. (27th February 2023) - Zhao, Jiangshan; Wang, Qingxuan; Xu, Guoqiang; Shi, Yunxing; Su, Youpo
Highlights: The diamond-indent feature of MSF provides favorable interfacial bond strength. MSF can compensate for the reduction in compressive strength caused by IOTs. The fracture energy of IOT concrete increases by up to 20.19-fold due to MSF. The relationship between the FRI and post-cracking behavior is developed. Abstract: Iron ore tailing (IOT) is a hazardous by-product of iron extraction, and its disposal has resulted in serious environmental issues. This paper investigated the interfacial bond performance of macro-synthetic fiber (MSF). The effect of the IOT replacement ratio on the compressive performance of concrete and the effects of MSF on the compressive and flexural performance of IOT concrete were evaluated. Test parameters included IOT replacement ratio (0%, 50% and 100%), fiber volume fraction (0%, 0.5%, 1.0%, 1.5% and 2%) and fiber aspect ratio (43, 60 and 69). The test results indicated that the deterioration in compressive strength was observed with the increase in the IOT replacement ratio. The mechanism of the effect of IOT on the compressive performance of concrete was analyzed. However, the incorporation of MSF compensated for the reduction in compressive strength caused by iron ore tailings (IOTs). Furthermore, the post-cracking performance, which includes residual flexural tensile strength, equivalent flexural tensile strength and fracture energy, of concrete increased with the increase in fiber volume fraction. The fracture energy of IOT concrete increased by a factor of 18.06–20.19, and the post-cracking performance of IOT concrete was comparable with that of natural sand (NS) concrete at an MSF fiber volume fraction of 2%. At a given fiber volume fraction, the MSF with a higher fiber aspect ratio was more effective in improving post-cracking performance than one with a lower aspect ratio. Moreover, new empirical equations were proposed, which can accurately predict the residual flexural tensile strengths and equivalent flexural tensile strengths. These results provide important implications for determining the contribution of MSF in strengthening and toughening IOT concrete.